A LEARNING OBJECT SUCCESS STORY - Mason, Robin; Pegler, Chris; Weller, Martin (Online Learning, 2005)
This paper outlines an approach to designing a course entirely in learning objects. It provides a theoretical basis for the design and then presents evaluation data from a master’s level course using this design. It also describes several re-uses of the learning objects on other courses and in different contexts. Each learning object is conceived as a whole learning experience, thus avoiding many of the problems associated with assembling components of disparate kinds.